Advocating for reproducibility - Harrison Dekker; Amy Riegelman (IASSIST Quarterly, 2020)
As guest editors, we are excited to publish this special double issue of IASSIST Quarterly. The topics of reproducibility, replicability, and transparency have been addressed in past issues of IASSIST Quarterly and at the IASSIST conference, but this double issue is entirely focused on these issues.